Pengenalan Etnomatematika Pada Rumah Adat Loura Kepada Siswa Kelas VIII SMPK ST. Paulus Karuni - Lede, Yulis Keremata; Making, Samuel Rex Mulyadi; Moza, Florida; Kondi, Sophi; Bili, Nopliana; Awa, Paramita Rusadi Legu (CV. Global Cendekia Inti, 2024)
The problem raised concerns the mathematical concepts contained in the Loura traditional house. The material presented is the result of research on the mathematical elements contained in the Loura traditional house. The activity was carried out in the form of a seminar for class VIII students at SMPK St. Paulus Karuni, which will be held in early February 2024. The stages of implementing this activity are preparation, implementation and evaluation. The preparatory stage is preparing ethnomathematics material with the team to be delivered to service partners. At the seminar implementation stage the presenter provides material to the 28 students with the core material being the shapes of traditional houses related to plane geometric shapes, and giving examples of questions related to roof of the Loura traditional house. Next, the evaluation stage of this activity was carried out by providing practice questions to students and students were also asked for their responses regarding the community service activities that had been carried out.